2018
DOI: 10.1128/jvi.01890-17
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Zipper Motifs in Hepatitis C Virus Nonstructural Protein 4B Are Required for the Establishment of Viral Replication Organelles

Abstract: Hepatitis C virus (HCV) RNA replication occurs in tight association with remodeled host cell membranes, presenting as cytoplasmic accumulations of single-, double-, and multimembrane vesicles in infected cells. Formation of these so-called replication organelles is mediated by a complex interplay of host cell factors and viral replicase proteins. Of these, nonstructural protein 4B (NS4B), an integral transmembrane protein, appears to play a key role, but little is known about the molecular mechanisms of how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…This compartmentalization of replication machinery allows the enrichment and coordination of cellular and viral factors required for RNA replication, and the evasion from innate host defense systems recognizing non-self RNAs such as 5′-triphosphorylated RNAs and double-stranded RNAs [5, 6]. Two distinct morphotypes of replication organelles have been reported, corresponding to the ‘invaginated vesicles/spherule type’ and the ‘double membrane vesicle (DMV) type’ [7]. DMVs are the major component of the HCV replication organelle [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compartmentalization of replication machinery allows the enrichment and coordination of cellular and viral factors required for RNA replication, and the evasion from innate host defense systems recognizing non-self RNAs such as 5′-triphosphorylated RNAs and double-stranded RNAs [5, 6]. Two distinct morphotypes of replication organelles have been reported, corresponding to the ‘invaginated vesicles/spherule type’ and the ‘double membrane vesicle (DMV) type’ [7]. DMVs are the major component of the HCV replication organelle [8].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation into the NS5A-mediated DMV formation revealed that NS5A domain 1 is required for the DMV formation [8]. Other viral protein(s) such as nonstructural protein 4B (NS4B) augments DMV formation activity of NS5A [7].…”
Section: Introductionmentioning
confidence: 99%
“…The observation that NS5A inhibitors (e.g., daclatasvir) block the HCV RO formation independent of RNA replication demonstrated the essential role of NS5A in the RO formation [ 28 ]. The efficiency of the DMV formation induced by NS5A alone is low but is greatly enhanced when the other nonstructural proteins are also expressed, e.g., NS4B, NS3, or NS5B [ 26 , 29 , 30 ].…”
Section: Viral Replication Organelles (Ro)mentioning
confidence: 99%
“…Moreover, NS4B contains a GXXXXGK P-loop for nucleotide triphosphate binding, which may be involved in membrane rearrangements [ 36 ]. In addition, NS4B could form homo-oligomeric complexes, which are required for the RO formation [ 29 , 37 , 38 ].…”
Section: Viral Replication Organelles (Ro)mentioning
confidence: 99%
“…Мелковезикулярное полотно представляет своеобразный рецепторный «аэродром» (репликативную «фабрику») в виде ремоделированных мембран на которых происходит репликация HCV. Ремоделированные мембраны представляют собой цитоплазматические накопления одно-, двух-и мультимембранных везикул в инфицированных HCV клетках [22,23,24]. Формирование таких репликационных органелл опосредуется сложным взаимодействием факторов клетки-хозяина и вирусных репликативных белков.…”
Section: результаты и обсуждениеunclassified